#TITLE_ALTERNATIVE# - Tunnisa (NIM : 11413028), Fitra
Brown rice have many benefits in health. It is known for diabetes, hemorrhoids, and constipation. The production of brown rice needs to be improved. Improvement in rice productivity can be achieved through the modification of cultivation methods namely SRI (System of Rice Intensification) and Drip Irrigation System. This study aims to compare the growth and productivity of rice plants cultivated using SRI and drip irrigation methods. The comparison was based on the difference in types of fertilizer added to the media. The fertilizers used in this research were NPK as a single form, compost, and the combination of both. The results were tested by one way ANOVA statistic test and continued test of Multiple Range Test Duncan 5%. The results showed that in the vegetative phase the highest RGR (Relative Growth Rate) and NAR (Net Assimilation Rate) were 0.139 g/g/day and 0.00226 g/cm2/day respectively, achieved after compost treatment. Moreover, the highest growth of plant height and number of leaves were 90.08 cm and 100 leaves respectively, achieved after the addition of both NPK and compost. Here also showed that the highest number of tiller (29 tillers) was achieved after addition of NPK as synthetic fertilizer. The highest dry grain weight and filled grains were 51.54 gram/plant and 41.44 gram/plant respectively as the results of compost addition. The largest percentage of unfertilized grains (40%) were achieved without addition of any fertilizer while the highest 1000-grain weight was showed after addition of NPK. The highest productivity of rice plants is achieved after compost treatment that is equal to 8.25 ton/ha/harvest. Using SRI and drip irrigation methods in cultivation of rice plant from the highest dry grain weight can improved productivity were 3.15% of yield potential and 37.5% of average yield.